Globalising Democracy - Burnell, Peter (Routledge Studies in Globalisation, 2006)
This volume brings together expert contributors to explore the intersection of two major contemporary themes: globalization, and the contribution that both domestic party politics and international party support make to democratization. Globalising Democracy clearly shows what globalization means for domestic and international efforts to build effective political parties and competitive party systems in new and emerging democracies. Contrasting perspectives are presented through fresh case studies of European post-communist countries, Africa and Turkey. The reader is clearly shown how international party assistance is a manifestation and vehicle of globalization, and explores how it may be assessed in terms of: global economic integration the growth of global communications the development and implications for party politics of multi-level governance. This is the first book to analyze the impact of globalization on democracy and will be of great interest to all students of international relations, governance and politics.